EASE OF USE, ONLINE CUSTOMER RATING, AND ONLINE CUSTOMER REVIEW: KEYS TO BUYING DECISIONS ON GRAB FOOD - Ramadhan, Tri Sugiarti (Universitas Pelita Harapan, 2024)
This study examines the influence of Ease of Use, Online Customer Rating, and Online Customer Review on Buying Decisions among Grab Food users in Malang City. The growth of food delivery apps has transformed consumer behavior in Indonesian urban areas, creating a research gap regarding how digital elements affect purchase decisions. Traditional decision-making models may not fully apply to mobile food delivery platforms. The population comprised of Grab Food users in Malang City, with data from 120 respondents. Multiple linear regression analysis via SPSS version 23 showed all three variables collectively significantly affected Buying Decisions. Individually, Ease of Use (β=0.381, p<0.01) and Online Customer Review (β=0.427, p<0.01) demonstrated positive and significant effects, while Online Customer Rating showed no statistically significant influence (β=0.103, p>0.05) on consumer purchase decisions.